1984
DOI: 10.1111/j.1365-2648.1984.tb00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles of nursing students and career choices

Abstract: Kolb's 'Learning Style Inventory' was used to examine learning characteristics of incoming nursing students (n = 166) which were then compared to those of more advanced nursing students (n = 102). A majority of students were found to have concrete learning styles. Advanced students had a greater incidence of concrete learning styles than first year students suggesting increasing concreteness with exposure to nursing education. Diploma students were found to have a higher incidence of concrete learning styles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 2 publications
2
18
0
1
Order By: Relevance
“…9 Nursing students tend to be more divergers or accommodators. 39,40 Medical students' learning styles shift from passive to more active preferences (eg, from assimilator or diverger to converger or accommodator) during the course of their training, 18 and we plan to study this relationship among pharmacy residents once they have been in practice for a year. Medical residents tend to be more active learners than medical students, 36 and lateryear medical students are more active learners than those in their early years.…”
Section: 1238mentioning
confidence: 99%
“…9 Nursing students tend to be more divergers or accommodators. 39,40 Medical students' learning styles shift from passive to more active preferences (eg, from assimilator or diverger to converger or accommodator) during the course of their training, 18 and we plan to study this relationship among pharmacy residents once they have been in practice for a year. Medical residents tend to be more active learners than medical students, 36 and lateryear medical students are more active learners than those in their early years.…”
Section: 1238mentioning
confidence: 99%
“…Several studies in the nursing literature have reported that students in nursing and other human service professions tend to fall into the concrete learning style preference, as defined by Kolb's Learning Style Inventory (Hodges, 1988;Huch, 1981;Laschinger & Boss, 1984). These findings support Kolb and Kolb's (2005a) contention that members of human service professions have concrete, people-oriented learning styles.…”
Section: Health Professions and Nursingsupporting
confidence: 52%
“…As students have varied learning styles, teaching requires diverse educational approaches at various levels of training (Gurpinar et al, 2010). This is good news as educators believe individuals use a mixture of different learning styles dependent upon the situation (Loo, 2004) and others (Laschinger and Boss, 1984) have stressed for decades the importance of including multiple types of learning activities alongside lecture so all learning styles can thrive. This is supported by Kolb who asserts that the key to effective learning is the ability to be flexibly competent in each mode when it is called for, but not to use all modes in every situation (A.…”
Section: Discussionmentioning
confidence: 99%
“…They include the Learning Style Questionnaire by Honey and Mumford, the Dunn and Dunn Learning Style Questionnaire, the Myers-Briggs Type Indicator, the Gregorc Style Delineator and the Learning Style Inventory (LSI) by Kolb. The Kolb LSI is a wellvalidated and reliable assessment instrument and often used in nursing studies (Cavanagh et al, 1995;Laschinger, 1986Laschinger, , 1992Laschinger and Boss, 1984;Lockie et al, 2013;O'Kell, 1988;Ostmoe et al, 1984;Remington and Kroll, 1990;Sulliman, 2006;Sutcliffe, 1993;Washington et al, 1990). Therefore, it was chosen for this study.…”
Section: Introductionmentioning
confidence: 99%